Synthesis of graphene oxide coated Nafion membrane for actuator application. Issue 3 (April 2015) - Surana, Karan; Singh, Pramod K.; Bhattacharya, B.; Verma, C.S.; Mehra, R.M.
Abstract: We have fabricated an ionic polymer metal composite (IPMC) actuator with polyaniline and graphene oxide composite as electrode over the widely used Nafion membrane, using a simple solvent mixing and dip coating process thus avoiding the costly and time-consuming platinum coating process. The proton conductivity, dielectric constant, water uptake potential, ionic transference number and X-Ray diffraction studies have been carried out along with monitoring the tip displacement of the actuator with varying D.C. voltages and time.